2019
DOI: 10.48550/arxiv.1908.00770
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Classification of tiling $C^*$-algebras

Luke J. Ito,
Michael F. Whittaker,
Joachim Zacharias

Abstract: We prove that Kellendonk's C * -algebra of an aperiodic and repetitive tiling with finite local complexity is classifiable by the Elliott invariant. Our result follows from showing that tiling C * -algebras are Z-stable, and hence have finite nuclear dimension. To prove Z-stability, we extend Matui's notion of almost finiteness to the setting of étale groupoid actions following the footsteps of Kerr. To use some of Kerr's techniques we have developed a version of the Ornstein-Weiss quasitiling theorem for gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…(2) Corollary 7.8 naturally applies to many minimal almost finite groupoids, such as certain minimal almost finite geometric groupoids introduced in [6] and groupoids of repetitive aperiodic tillings of R d with finite local complexity, e.g., Penrose tillings, considered in [9].…”
Section: Xin Mamentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Corollary 7.8 naturally applies to many minimal almost finite groupoids, such as certain minimal almost finite geometric groupoids introduced in [6] and groupoids of repetitive aperiodic tillings of R d with finite local complexity, e.g., Penrose tillings, considered in [9].…”
Section: Xin Mamentioning
confidence: 99%
“…The main obstruction is that, in a general fiberwise amenable groupoid G, so far there has been no topological tiling results for any compact "Følner" set that is applicable to general groupoids. However, we remark that it was developed a version in [9] that is applicable to certain tilling groupoids. Nevertheless, the methods developed in [13] called extendability and almost elementariness actually are good enough here to construct an c.p.c order-zero map from matrix algebras to the groupoid algebras.…”
Section: Introductionmentioning
confidence: 99%
“…Example 9.13. Recently, in [IWZ19], Ito, Whittaker and Zacharias established Zstability of Kellendonk's C * -algebra of an aperiodic and repetitive tiling with finite local complexity through generalizing the approach for group actions in [Ker20] to groupoid actions. In addition, they showed that such a C * -algebra is a reduced C * -algebra of a locally compact Hausdorff étale second countable minimal principle almost finite tiling groupoid.…”
Section: Then We Can Do the Same Decomposition Process For All Multis...mentioning
confidence: 99%
“…Inspired by the Følner set approach to (group-theoretic) amenability, Matui [Mat12] introduced a more general notion called almost finite groupoids 1 , which, like AF groupoids, also applies to ample étale groupoids, but it only demands that every compact subset of a topological groupoid is almost contained in an elementary subgroupoid in a Følner-like sense. Almost finiteness strikes a remarkable balance between applicability and utility: it was shown to be enjoyed by transformation groupoids arising from free actions on the Cantor set by Z n (later generalized in [KS20]; see below), as well as those arising from aperiodic tilings ( [IWZ19]); on the other hand, this notion has found applications in the homology theory of ample groupoids, topological full groups, and the structure theory and K-theory of reduced groupoid C * -algebras, and deep connections to an increasing number of other important properties have been established (see, for example, [Mat15,Mat17,Nek19,Ker20,Suz20]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation